2005
DOI: 10.1074/jbc.m506711200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Agonist-induced Conformational Change Occurring Adjacent to the Ligand-binding Pocket of the M3 Muscarinic Acetylcholine Receptor

Abstract: To study the conformational changes that convert G protein-coupled receptors (GPCRs) from their resting to their active state, we used the M 3 muscarinic acetylcholine receptor, a prototypical class A GPCR, as a model system. Specifically, we employed a recently developed in situ disulfide cross-linking strategy that allows the formation of disulfide bonds in Cys-substituted mutant M 3 muscarinic receptors present in their native membrane environment. At present, little is known about the conformational change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 59 publications
8
44
0
Order By: Relevance
“…The interpretation was that TM-III and TM-VII at this level of the receptor will have to move closer to each other during activation. This is again in agreement with our toggle switch model based on metal ion site engineering, including a site between positions III:08 and VII:06 located one helical turn "above" the residues used for disulfide bridge formation in the M3 receptor (21,49).…”
Section: Global Toggle Switch Model For Helical Movements During 7tmsupporting
confidence: 76%
“…The interpretation was that TM-III and TM-VII at this level of the receptor will have to move closer to each other during activation. This is again in agreement with our toggle switch model based on metal ion site engineering, including a site between positions III:08 and VII:06 located one helical turn "above" the residues used for disulfide bridge formation in the M3 receptor (21,49).…”
Section: Global Toggle Switch Model For Helical Movements During 7tmsupporting
confidence: 76%
“…Upon 7TM receptor activation, the top of TM-III and -VI move closer, and it has been speculated that an inverse agonist functions as a wedge preventing these helices from approaching each other (28,29). In agreement with this hypothesis, it has been shown that III:04/3.36 and VII:09/7.42 in fact move close together upon activation of the M3 muscarinic receptor (43). Thus, given that GSK682753A probably resides between these residues, it can be speculated that the compound inhibits the constitutive activity of EBI2 by preventing TM-III and -VII from approaching each other.…”
supporting
confidence: 57%
“…Cells were transfected with 4 g/dish of receptor plasmid DNA using the Lipofectamine Plus kit (Invitrogen), according to the manufacturer's instructions. To achieve higher receptor expression levels, transfected cells were incubated with 1 M atropine for the last 24 h of culture, as described previously (23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…To monitor ligand-induced changes in receptor structure, we employed an in situ disulfide cross-linking strategy that allows the detection of disulfide bond formation between Cys residues that are adjacent to each other in the three-dimensional structure of the receptor (23)(24)(25)(26). One major advantage of this strategy is that ligand-dependent conformational changes can be detected in receptors present in their native membrane environment, without the need for any receptor purification and reconstitution steps.…”
mentioning
confidence: 99%